Trajectories in physical functioning at older age in relation to childhood and adulthood SES and social mobility: a population-based cohort study - Pająk, Andrzej; Polak, Maciej; Kozela, Magdalena; Doryńska, Agnieszka; Bobak, Martin (Frontiers in Public Health, 2023)
Introduction: Older age is associated with the deterioration of physical functioning (PF), and low PF is strongly related to poor quality of life among older people. We conducted a study to examine the trajectories of PF between middle and old age, considering sex differences, as well as the association between socioeconomic status (SES) at different life stages and changes in PF.We analyzed data from the Polish arm of the HAPIEE (Health Alcohol and Psychosocial factors in Eastern Europe) study, including 1116 men and 1178 women aged 45-64 years at baseline. Adult and childhood SES, as well as social mobility, were assessed using a retrospectively focused questionnaire. PF was assessed using the 10-question SF-36 scale at baseline examination, face-to-face re-examination, and in three postal surveys, covering up to 20 years (on average, 18 years). We employed Generalized Estimating Equations models to assess changes in PF scores over time and compare PF trajectories across different SES categories.After adjusting for age and other covariates, we found that, in both sexes, participants with always middle or high SES, as well as those who reported upward mobility, had higher PF scores at baseline compared to those with always low SES. A decline in PF between middle and old age was observed in all SES groups; however, the decline was slower in participants with always middle or high SES compared to those with always low SES.This cohort study revealed that lower SES and downward social mobility were crosssectionally associated with poorer PF, while upward social mobility seemed to largely reverse the effect of low childhood SES. In addition to the cross-sectional associations observed at baseline, advantaged SES was also significantly associated with a slower decline in PF over an 18-year follow-up period.